Prevalencia de estrés y ansiedad en los habitantes diagnosticados con Covid-19 del Barrio Progresar en Tuluá - Valle (2022)
The objective of this research was to determine the prevalence of stress and anxiety in the inhabitants between 20 and 60 years of age of the Progresar neighborhood of Tuluá-Valle, analyzing the presence of clinical symptoms, and determining the frequencies of distribution of mental health indicators of the same students.